"How Could any One Relationship Ever Possibly be Fulfilling?": Bisexuality, Nonmonogamy, and the Visualization of Desire in the Cinema of Gregg Araki. Issue 1 (2nd January 2018) - Engelberg, Jacob
ABSTRACT: The cinematic oeuvre of Gregg Araki is populated with invocations of bisexuality. Many of Araki's characters desire people of more than one gender and their desires are routinely represented in ways that resist the trend of bisexual erasure within media. This article examines the techniques through which bisexuality is thus rendered intelligible within a fatalistically monosexist signifying economy. This article argues that Araki's cinema often visualizes bisexuality within this economy by yoking bisexual desire to visual representations of nonmonogamy. Although these representations render some images of bisexual desire visible, they also preclude others from visibility and buttress bisexual stereotypes related to fulfilment, infidelity, and excess. Although the yearning for representation, like many of Araki's characters, may be inexorably doomed, this article concludes that the techniques through which Araki invokes bisexuality are indicative of the manifold ways in which monosexuality's sovereignty in the visual thwarts bisexuality's cinematic intelligibility.